SPEECH ACTS ANALYSIS OF DONALD TRUMP’S SPEECH - Nura Siti Mufiah; Muhammad Yazid Nur Rahman (IKIP Siliwangi, 2018)
This research deals with the types of illocutionary acts in Donald Trump’s Inaugural Speech. The research concerns with illocutionary act produced by Donald Trumps as a President of American. The aim of this research was to analyze the types of illocutionary speech act which was dominantly used in that speech. This research applied descriptive qualitative method and speech act theory by Yule. There were 63 utterances and the percentage of utterances were Representative 46%, Expressive 11%, Directive 16%, Commissive 12,7%, and Declarative 14,3%. The result showed that Donald Trump assert to the audience about the nation will be.It is found that Trump’s speech acts in his speech are intended as statement of fact and assertion. Disscussion of hopes implied in Trump’s speech acts. As seen on the table above, it can be seen that Trump hoped that his audiences would be persuaded to act